THU0338 A Randomized, Placebo-Controlled Study to Evaluate Efficacy and Safety of A Dietary Supplement Containing Mucopolysaccharides, Collagen Type I and Vitamin C for Management of Different Tendinopathies. (10th June 2014) - Hai Binh, B.; Ramirez, P.; Martinez-Puig, D.
Abstract : Background: Overuse tendon injury (tendinopathy) occurs in loaded tendons of the upper and lower limb and results in pain, decreased exercise tolerance of the tendon and a reduction in function. Characteristic changes occur in tendon structure, resulting in a tendon that is less capable of sustaining repeated tensile load. Objectives: The aim of this study was to evaluate the efficacy and safety of a food supplement containing mucopolysaccharides, collagen type I and vitamin C on the clinical symptoms, pain and tendon structure of patients with tendinopathy of Achilles, supraspinatus, lateral epicondyle or plantar fasciitis. Methods: Patients with clinically and sonographically diagnosed tendinopathy were randomized to receive two capsules per day of Tendoactive® (TA) (435mg of mucopolysaccharides, 75mg of collagen type I and 60mg of vitamin C) or two identical capsules of placebo (PBO) during 90 days. An oral NSAID (Mobic® 7.5 mg/day) was allowed in both groups as rescue medication for a maximum of 30 days. Patients were monitored monthly during the study period. Clinical assessments included presence/absence of clinical symptoms (swelling, burn and redness) and pain intensity using a visual analog scale (VAS). Tendon structure was characterized sonographically and presence/absence of tendinopathy was reported. Results: A total of 60 patients were included, 30 assigned to each treatment group. Average age was 41, 4±1, 50 years in TA group and 40, 2±0, 26 years in PBO group. They were mostly women in both groups (83.3% and 86% in TA and PBO groups respectively). The percentage of patients presenting each clinical symptom was progressively reduced in both groups, reaching lower values in the TA group at each time point. Pain level assessed by VAS was comparable between groups at baseline (5, 82±0, 21 vs 5, 71±0, 23 in TA and PBO groups respectively). It was significantly reduced in both groups during the study period, but patients supplemented with TA had significantly lower pain value at 90 days (2, 5±0, 22 vs 3, 20±0, 20 in TA and PBO groups respectively; P<0.05). At the end of study, no patient in the TA group was diagnosed for tendinopathy according to ultrasounds assessment. Conclusions: The overall results of this randomized, placebo-controlled study show that Tendoactive® supplementation is a safe and effective therapeutic option to improve both clinical symptoms and structural evolution of injured tendons as demonstrated in Achilles, supraspinatus, lateral elbow epicondyle and plantar fasciitis. References: F. Nadal, T. Bové, D. Sanchís, D. Martinez-Puig. Effectiveness of treatment of tendinitis and plantar fasciitis by Tendoactive. Osteoarthritis and Cartilage 2009;17(1):S253 M. Shakibaei, C. Buhrmann and A. Mobasheri. Anti-inflammatory and anti-catabolic effects of TENDOACTIVE® on human tenocytes in vitro. Histology and Histopathology 2011;26:1173-1185 Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5477